Implementasi Metode Ice Breaking Untuk Meningkatkan Motivasi Belajar Siswa Pada Pembelajaran Fiqih - Rohmadi (Jurnal Ilmu Pendidikan Islam, 2023)
During the learning process, motivation is needed to encourage and encourage students to be motivated in achieving the desired learning goals. This study aims to increase students’ motivation, enthusiasm for learning by using Ice Breaking method, to determine students’ learning motivation before and after the implementation of the Ice Breaking learning through fiqih material during the new normal period at MTs N 1 Palembang in class IX.J This Researcher uses a pre-eksperimental type of research (pre-experimental) with a one –grup pretest-posttest design. The popation in this study is all 152 students of class IX MTs N 1 Palembang. Determining the sample using purposivesampling technique. Then through, data collection techniques through questionnaires and documentation as well as data analysis techniques using validity testing, realiability testing and hypothesis testing using t test (paired samples test) through SPSS Version 23. From the results obtained in this study and the analysis can be seen from the average score of students’ learning motivation before classified as high as 7 students (24%), classified as moderate 7 students (24,1%), and classified as moderate 15 students (51%). And from the average score of students’ learning motivation after the Ice Breaking method was applied, namely students who were classfied as higt as many as 9 students (27,5%), classified as medium 12 students (41,3%), and classified as low 9 students (32%). Meanwhile, based on the t test analysis (paired samples test) obtained as sig value of 0.00 which is smaller than 0.05 (0,00 < 0,05) thus it can be concluded that ho is rejected and Ha is accepted which means there is an increase or difference in student learning motivation between before and after applying the Ice Breaking method